Clinical features, microbiological profile and treatment outcome of patients with Corynebacterium endophthalmitis: review of a decade from a tertiary eye care centre in southern India. Issue 2 (29th June 2015) - Joseph, Joveeta; Nirmalkar, Khemlal; Mathai, Annie; Sharma, Savitri
Abstract : Aims: To report the clinical and microbiological profile along with treatment outcome of patients with endophthalmitis caused by Corynebacterium sp. Methods: This is a retrospective, consecutive, non-comparative case series of patients with culture-proven Corynebacterium endophthalmitis seen between August 2004 and July 2014. Results: Of 5439 patients clinically diagnosed as infective endophthalmitis, vitreous samples were culture positive for bacteria in 1488 (27%). Sixteen patients (1%) were identified as Corynebacterium endophthalmitis. The clinical settings included trauma (n=10), post-cataract surgery (n=5) and post-penetrating keratoplasty (n=1). In 7/16 (44%) patients, the organisms were visualised in direct microscopy. Tested by disc-diffusion method, all isolates were vancomycin sensitive. However, 9 of 10 isolates were resistant to ceftazidime and 5 of 14 isolates were resistant to amikacin. Initial treatment strategies included pars plana vitrectomy with intravitreal antibiotics (vancomycin and amikacin/ceftazidime) injection (n=9) and pars plana lensectomy along with pars plana vitrectomy and intravitreal antibiotics (vancomycin and amikacin/ceftazidime) injection (n=7). Final visual acuity was 20/200 or better in 11 (69%) of 16 patients. Conclusions: The prevalence of corynebacterial endophthalmitis is low. The organisms are susceptible to vancomycin, and early appropriate treatment results in favourable outcome.